2020
DOI: 10.1002/chem.201905753
|View full text |Cite
|
Sign up to set email alerts
|

Stiff‐Stilbene Ligands Target G‐Quadruplex DNA and Exhibit Selective Anticancer and Antiparasitic Activity

Abstract: G‐quadruplex nucleic acid structures have long been studied as anticancer targets whilst their potential in antiparasitic therapy has only recently been recognized and barely explored. Herein, we report the synthesis, biophysical characterization, and in vitro screening of a series of stiff‐stilbene G4 binding ligands featuring different electronics, side‐chain chemistries, and molecular geometries. The ligands display selectivity for G4 DNA over duplex DNA and exhibit nanomolar toxicity against Trypasanoma br… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 31 publications
(70 reference statements)
1
31
0
Order By: Relevance
“…Several derivatives were later developed, (290) and studied for their G4-stabilising properties, along with their antiproliferative activity against T. brucei parasite and HeLa cancer cells. NMR titrations confirmed the ability of bispyridinium stiff-stilbenes to disrupt the external G-quartet upon binding (1:2 G4:ligand ratio, in K + -conditions), which was also reported with a bispyridinium dithienylethene (DTE) derivative (at 1:3.6 G4:ligand ratio in both K + and Na + ).…”
Section: B How To Destabilize G-quadruplexes and Why?mentioning
confidence: 99%
“…Several derivatives were later developed, (290) and studied for their G4-stabilising properties, along with their antiproliferative activity against T. brucei parasite and HeLa cancer cells. NMR titrations confirmed the ability of bispyridinium stiff-stilbenes to disrupt the external G-quartet upon binding (1:2 G4:ligand ratio, in K + -conditions), which was also reported with a bispyridinium dithienylethene (DTE) derivative (at 1:3.6 G4:ligand ratio in both K + and Na + ).…”
Section: B How To Destabilize G-quadruplexes and Why?mentioning
confidence: 99%
“…Ligands of type 3, where the stiff-stilbene core is appended to flexible alkyl spacer terminated in a basic moiety (protonated at physiological pH) also bind appreciably to G4 DNA (ΔTm = 12 °C at 10 μM ligand concentration). 35 However, the interaction is weaker than for pyridinium ligands 1 and 2, perhaps a result of the more flexible nature of the side chains which provide additional degrees of freedom in the unbound ligand. Figure 3 depicts the binding conformations sampled in MD simulation of ligand 3 on the lowest-energy binding pose found in preliminary docking calculations.…”
Section: Antiparallel Telo22 Is Stabilized By Low Concentrations Of Mmentioning
confidence: 99%
“…We recently reported the design and synthesis of a novel family of stiff-stilbene G4 ligands (1-5, Figure 1). 35,36 The lead compound 1 displays high G4 thermal stabilization (ΔTm = 21 °C) and discrimination against duplex DNA (ΔTm = <1 °C), as well as interesting promise as the basis of anticancer and antiparasitic therapies, being toxic in the nanomolar range against HeLa cells whilst remaining 30-fold less toxic to non-tumoral mammalian cells. Through a variety of experimental approaches, we observed that the effect of ligand on G4 was sensitive to the nature of the ligand geometry, functionality and the nature of the G4 topology and metal cation.…”
Section: Experimental Approach and Selection Of G4/ligand Modelsmentioning
confidence: 99%
“…[30] Nevertheless,Galan and co-workers noted that decomposition of E-43 caused the Gquadruplex DNAtore-adopt its original topology and hence, by cycles of irradiation and E-43 addition, the conformation could be controlled in ar eversible manner.I nasubsequent study,the same group demonstrated that the strong binding of E-43 to G-quadruplex DNAp romotes toxicity towards cancerous cells. [71] In another recent study,Míšek and Luptak described that the photocontrol of binding of as tiff-stilbene amino alcohol to m-RNAc an be used to regulate protein expression. [72]…”
Section: Toward Biological Applicationmentioning
confidence: 99%